Communication Pattern of Kyai and Santri at TarbiyatulWildan Islamic Boarding school in Karawang Regency - Nursanti, Siti; Rifai, Maulana; Fakhrudin, Dadang; Hakim, Lukmanul (International Journal of Engineering and Technology, 2018)
Pondok Pesantren Tarbiyatul Wildan in Rawa is an educational institution intended for children 5 years to 7 years old. The age is quite unique because usually children at such ages are in need of the family. This research will discuss about the meaning of santri or students for kyai or teachers who play the role of teachers and parents at the same time. This study uses a case study approach where the resource persons are drawn from different angles. In this study found the result that kyai has a function as a teacher, friends as well as parents at the same time. Various problems arise in the management of educational institutions which certainly appeals to a kyai more patient and understand the students builtÂ Â